Application of Cooperative Learning Model Think Pair Share Type to Increase Students' Self Confidence Islamic Religious Education Subjects - Nasrulloh, Muhammad Farid; Ma'ruf, Mochammad; Khotimah, Khusnul; Maksum, Mohammad Ja'far Sodiq (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The aim of this research is to find out how effective the application of Think, Pair, Share nature is in increasing the self-confidence of students in class IX in PAI subjects. The research method used uses quantitative research. The research carried out is quantitative research. The experiment in this research is a quasi experimental design type experiment. This research aims to measure the application of the Think, Pair, Share type cooperative learning model in increasing self-confidence student. The population of this study includes all class IX students of SMPN 1 Kunjang for the 2023/2024 academic year. Meanwhile, sampling was carried out using a purposive sampling technique and it was found that the research sample classes were students from classes IX-F and IX-G, consisting of 72 students with 36 students in each class. Data collection techniques were carried out using objective tests in the form of pretest and posttest assessments and non-tests in the form of self-confidence questionnaires, observations and interviews. Researchers used Levene's Test. In this study, the hypothesis test used was comparative using SPSS 26.00 for Windows to calculate the t test for two independent samples (Independent-samples t-test) and two interconnected samples (Paired-samples t-test). the application of the Think Pair Share (TPS) learning model is able to increase students' self-confidence in PAI subjects in class IX at SMP Negeri 1 Kunjang.